Alerte sur le front de l’art. Marguerite Burnat-Provins et la guerre 1914-1915 - Claude Menges-Mironneau; Paul Mironneau (In Situ)
Marguerite Burnat-Provins (1872-1952) was a poetess and painter whose work has been rediscovered over the past fifteen years. She was an uncompromising character. The series of articles she submitted to the Journal de Bayonne between the summer of 1914 and the autumn of 1915 was addressed to ‘the neutrals’, whether nations or individuals, accusing them all of faint-heartedness. These opinion pieces can be read as a cry of anguish for lost heritage, a sense of the cultural world being laid to waste: the cathedral at Rheims, the belfry at Arras, the long list of scarred landscapes... They reveal an ambitious work of invention, seeking to replace the lost and regretted heritage with an original and visionary form that announces the aesthetic attitudes of the inter-war years. Marguerite Burnat-Provins indeed undergoes an important interior artistic transformation during these years, revealing an insurgent poetical stance, a ‘hallucinatory talent’ that succeeded her years of ruralism and her earlier art nouveau inspiration.